A novel robust event‐triggered fault tolerant automatic steering control approach of autonomous land vehicles under in‐vehicle network delay - Zhang, Jie; Zhang, Bangji; Zhang, Nong; Wang, Chenyang; Chen, Yuanchang (International journal of robust and nonlinear control, 2021)
This paper proposes a novel robust event‐triggered fault tolerant automatic steering control strategy for autonomous land vehicles to achieve path tracking and vehicle lateral motion control under in‐vehicle network delay. From the practical point of view, the parameter uncertainties, time delay, and actuator fault are simultaneously introduced to make the designed controller robust to more extensive and challenging driving conditions. A novel polytope reduction and norm‐bounded uncertainty reduction method is used to effectively handle the time‐varying velocity and tire cornering stiffness uncertainties. Then, the uncertain vehicle model can be reconstructed as an uncertain network control system model with time delay and actuator fault. Due to the inevitable time delay and actuator fault, a new cubic absolute‐value Lyapunov function is developed to guarantee the asymptotical stability of the closed control system with the H∞ performance, and the modified project‐based adaptive law is applied to strengthen the fault tolerant ability. Furthermore, a progressive event‐triggered mechanism is proposed for the collaborative design of robust fault tolerant automatic steering controller, which can signally improve the communication resource utilization of the limited bandwidth in‐vehicle network. Finally, the performance comparisons of different controllers are presented. These results prove that the proposed controller can simultaneously guarantee the path tacking performance and lateral dynamics stability, and save the communication resource of the in‐vehicle network.